Physical Fitness Survey of Grade VI Students of Public Elementary School 2 Kebumen for the 2022/2023 School Year - Solekhah, Nur; Raman, Arumugam (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The purpose of this study was to determine the physical fitness of grade VI students of Elementary School 2 Kebumen. The method used is quantitative descriptive research with survey methods. The subjects in this study were 23 grade VI students of SD Negeri 2 Kebumen, consisting of 13 students and 10 students. The sampling method uses the total sampling method. Nusantara Student Fitness Test 2022 is a series of TKPN tests consisting of five tests, namely: (1) Body Mass Index Test The purpose of this test is to determine the status of body mass (2) V Sit Reach Test This test aims to measure the flexibility of the back muscles and hamstrings. (3) Sit Up 60s this test aims to measure the strength and endurance of the abdominal muscles. (4) Squat Trust 30 seconds, Squat thrust is a combination movement of changing body position from standing position, squatting then push up position and back standing. The goal is to measure the endurance ability of strength, body control, balance, coordination and agility.and (5) Pacer Test, the Progressive Aerobic Cardiovascular Endurance Run (PACER) Test is a progressive aerobic cardiovascular endurance test using alternating cardiovascular endurance at a distance of 20 meters with step speed increasing every minute following a predetermined rhythm. Based on the results of research and discussion, the researchers concluded that the physical fitness level of grade 6 students of State Elementary School 2 Kebumen as measured by TKPN 2022 obtained an average result of 23 students having a